Abraham Abulafia$1 (Bs Esotericism Secrets and Doubtss - Idel, Moshe (Berlin/Boston De Gruyter, 2020)
This book focuses on Abraham Abulafia$1 (Bs esoteric thought in relation to Maimonides, Maimonideans, and Islamic thought in the line of Leo Strauss$1 (Btheory of the history of philosophy. A survey of Abulafia$1 (Bs sources leads into an examination of the esoteric meaning on the famous parable of the three rings, as well as Abulafia$1 (Bs universalistic understanding of the nature of the Bible, the Hebrew language, and the people of Israel.s
English
Keywords: Religion & beliefs; Judaism; Jewish studies; Medieval philosophy, Kabbalah, esotericism, Maimonides